THE USE OF INFORMATION TECHNOLOGY FOR EMBROIDERY ENTREPRENEURS - Anis Nusron; Margono Setiawan; Noermijati Noermijati; Rofiaty Rofiaty (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2022)
This study aims to examine the effect of entrepreneurial behavior and information technology on the performance of online entrepreneurs. This study uses a quantitative approach. The population in this study is embroidery business actors in Pasuruan Regency, East Java, who sell their products online. The sample in this study was 180 respondents. The data used was primary data which was processed using WarpPLS 6.0. The results showed that perceived usefulness had no effect on company performance, but perceived ease of use and entrepreneurial behavior in online selling significantly affected company performance. Perceived usefulness had no effect on entrepreneurial behavior in online selling, while perceived ease of use significantly affected entrepreneurial behavior in online selling. Entrepreneurial behavior in online selling did not mediate the effect of perceived usefulness on performance. In contrast, entrepreneurial behavior in online selling partially mediated the effect of perceived ease of use on company performance.